Caracterização morfológica, filogenética e patogênica de Chrysoporthe spp. associado ao cancro em Eucalyptus spp. e Tibouchina spp. - Santos, Thaissa de Paula Farias dos (2015)
Chrysoporthe spp. are known as canker of the pathogen in commercial plantations of Eucalyptus spp. and other hosts of Myrtaceae and Melastomataceae family. Cause canker in tree trunks, reducing their growth, leading to rupture of rods and even death of the plant. This work investigated whether other species or phylogenetic lineages of Chrysoporthe occurred in Brazil, besides of C. cubensis. Pathogenicity tests and cross inoculation were conducted to evaluate the resistance of 10 Eucalyptus clones and whether a pathogen specificity for the fungus host. Twenty isolates were submitted to analysis of molecular phylogeny of three gene regions: ITS, beta-tubulin and actin. Phylogenetic analysis Maximum parsimony and Bayesian inference sequences combined the three regions studied grouped the tested isolates into three groups. Isolates belonging to group 1, collected in Sao Joao del Rei and Tiradentes, MG, formed a distinct clade and not grouped with any species of Chrysoporthe reported in the literature. The morphological characterization of these isolates revealed that it is a new species that occurs in Brazil, due to differences in spore size, conidiophores. Isolates belonging to group 2 grouped with C. doradensis, species occurring in the country had not been reported until this study. This result was concerned with those obtained by morphological evaluation, as presented dimensions of equivalents tested morphological characters to those described for C. doradensis. Group 3 isolates clustered with C. cubensis and their classification was confirmed by morphological characterization. Pathogenicity tests conducted in quaresmeira and eucalyptus have shown no specificity of the pathogen to the host. The eucalyptus clones tested were classified into 4 groups and resistance was observed that the isolate of C. cubensis was more virulent than the isolated C. dorandesis tested. These results contribute to the knowledge of species Chrysoporthe occurring in Brazil and its virulence to present hosts in the country. Breeding programs that seek after the pathogen eucalyptus resistance will benefit from this knowledge about the true diversity of the pathogen in the country.